Participatory management in public institutions – The case of communal cultural organizations - Kowalik, Wojciech (Journal of Public Governance, 2018)
The article provides an overview of the relationship between culture and development and shows the role of cultural organizations in this process. The way to social and economic development, among other things, leads through efficient cultural organizations that use participatory tools and openness to help to multiply social and cultural capitals. The article presents research findings on how local cultural organizations utilize participatory management tools.